Equestris Ordo: Chivalry as a Vocation in the Twelfth Century - Morris, Colin (Studies in church history, 1978)
The motives of individuals are necessarily conditioned by the expectations of society. Some walks of life are recognised as demanding a high degree of self-sacrifice and noble motivation, as being (in modern terms) vocations. Others are careers worthy of esteem, and yet others are condemned, so that it is supposed that no ethically minded person would engage in them. As the social structure changes there is an adaptation in the pattern of esteem, and an interesting example of this process is provided by the new thinking about knighthood which emerged in the late eleventh and early twelfth centuries. So much has been written about chivalry that a broad review of the subject is out of the question in this paper, but it may be of interest to re-examine it in the light of this theme. An appropriate starting-point is provided by a passage from the history of the first crusade written about 1110 by Guibert of Nogent:In our time God has instituted holy warfare so that the knightly order (ordo equestris) and the unsettled populace, who used to be engaged like the pagans of old in slaughtering one another, should find a new way of deserving salvation. No longer are they obliged to leave the world and choose a monastic way of life, as used to be the case, or some religious profession, but in their accustomed liberty and habit, by performing their own office, they may in some measure achieve the grace of God.